2011
DOI: 10.1890/11-0559.1
|View full text |Cite
|
Sign up to set email alerts
|

Food webs and fishing affect parasitism of the sea urchinEucidaris galapagensisin the Galápagos

Abstract: In the Galápagos Islands, two eulimid snails parasitize the common pencil sea urchin, Eucidaris galapagensis. Past work in the Galápagos suggests that fishing reduces lobster and fish densities and, due to this relaxation of predation pressure, indirectly increases urchin densities, creating the potential for complex indirect interactions between fishing and parasitic snails. To measure indirect effects of fishing on these parasitic snails, we investigated the spatial relationships among urchins, parasitic sna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 42 publications
2
30
0
Order By: Relevance
“…In the Atlantic lowlands of Costa Rica, McKenzie (2007) found that, among three species of amphibian hosts collected from clear-cut cattle pasture and forest habitats, six metazoan parasite species were more abundant in pasture than forest, two species were more abundant in forest than pasture, and 13 species did 3 Present address: Department of Ecology and Evolutionary Biology, University of Colorado, Boulder, Colorado 80309 USA. Some have found higher parasite abundance and diversity in reserves than in open-access areas (Sasal et al 1996, Bartoli et al 2005, Loot et al 2005, Wood et al 2013, while others have found higher parasite abundance in open-access areas (Sonnenholzner et al 2011), or have failed to find significant differences in abundance and diversity between reserve and openaccess areas (Ternengo et al 2009). Aeby et al (2011) found that, while prevalence of growth anomalies (a tumor-like disease of unknown etiology) of Porites spp.…”
Section: Introductionmentioning
confidence: 99%
“…In the Atlantic lowlands of Costa Rica, McKenzie (2007) found that, among three species of amphibian hosts collected from clear-cut cattle pasture and forest habitats, six metazoan parasite species were more abundant in pasture than forest, two species were more abundant in forest than pasture, and 13 species did 3 Present address: Department of Ecology and Evolutionary Biology, University of Colorado, Boulder, Colorado 80309 USA. Some have found higher parasite abundance and diversity in reserves than in open-access areas (Sasal et al 1996, Bartoli et al 2005, Loot et al 2005, Wood et al 2013, while others have found higher parasite abundance in open-access areas (Sonnenholzner et al 2011), or have failed to find significant differences in abundance and diversity between reserve and openaccess areas (Ternengo et al 2009). Aeby et al (2011) found that, while prevalence of growth anomalies (a tumor-like disease of unknown etiology) of Porites spp.…”
Section: Introductionmentioning
confidence: 99%
“…In the Galapagos, removal of large fish predators reduces predation pressure on crabs that live commensally with sea urchins. Because those crabs eat the eulimid snail parasites of their urchin hosts, the resulting increase in commensal crabs reduces the epidemiological abundance of eulimid snails parasitic on sea urchins in open‐access relative to protected areas (Sonnenholzner, Lafferty & Ladah ). This variety of results – in which fishing can increase, decrease or not affect parasite abundance – highlights the potential complexity of effects of fishing on parasites.…”
Section: Introductionmentioning
confidence: 99%
“…;Lafferty et al 2008b;Freeman and MacDiarmid, 2009;Ternengo et al 2009;Marzoug et al 2012;Sonnenholzner et al 2011;Sala-Bozano et al 2012;Wootton et al 2012;Wood et al 2013).…”
mentioning
confidence: 99%